Determinants of net profit margins in foreign islamic banks: evidence from Malaysia - Maisyarah Stapah @ Salleh; Nizam Ahmat; Siti Nur Aqilah Ab Wahab; Nurhafiza Abdul Kader Malim (Human Resource Management Academic Research Society (HRMARS), 2024)
This study investigates the determinants of the Net Profit Margins (NPM) of foreign Islamic banks in Malaysia between 2008 and 2022. Using the fixed-effects estimator technique, we find positive and significant effects of risk aversion, overhead cost, total assets, gross domestic product growth, and market share loan on the NPM of foreign Islamic banks. Conversely, higher total weighted risks, capital adequacy ratio, total loan, and inflation are found to negatively impact the NPM. The analysis clearly indicates that both internal and external factors significantly influence the profitability of foreign Islamic banks. This research highlights the critical role of effective management strategies in mitigating risks while ensuring profitability. The findings provide valuable guidance for Islamic banks, policymakers, and regulators in formulating strategies to enhance the performance and sustainability of foreign Islamic banks in Malaysia. These insights can also be leveraged to balance financial stability with long-term profitability in the sector